Tinta Emosi: Petualangan Puisi Saat Galau Yang Menginspirasi - Henny Futry Ananti; Jumadi Jumadi; Dwi Wahyu Candra Dewi (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2024)
Poetry is an art form that allows writers to express troubled feelings with beautiful and deep words. This journal, “Emotional Ink: An Inspiring Poetry Adventure When You're Upset,” explores the relationship between anxiety and creativity in poetry. In the introduction, this journal introduces the importance of poetry as a unique medium of expression and provides an overview of the research aims. The research method uses a literature review to gain in-depth insight into leadership and team productivity. The results and discussion explain the role of poetry as a means of emotional expression and psychological therapy, while the conclusions highlight the power of poetry as a healing tool during difficult times.